Polyanionic Polydentate Europium Complexes as Ultrabright One‐ or Two‐photon Bioprobes. Issue 23 (30th October 2018) - Sund, Henri; Liao, Yuan‐Yuan; Andraud, Chantal; Duperray, Alain; Grichine, Alexei; Le Guennic, Boris; Riobé, François; Takalo, Harri; Maury, Olivier
Abstract: A family of europium (III) complexes based on a polydentate ligand functionalized by charge‐transfer antennae presents remarkable one‐ and two‐photon photophysical proper‐ties in water or buffer. A detailed analysis of their emission properties suggests that the wrapping of the ligand around the central rare‐earth ion results in an overall Cs symmetry in agreement with the theoretical simulation and that about 65–70 % of the emission intensity is concentrated in the hypersensitive 5 D0 → 7 F2 transition at 615 nm. Their brightness is excellent, in the range of the best lanthanide bioprobes making them very attractive for bio‐imaging experiments. Abstract : A family of europium (III) complexes based on a polydentate ligand functionalized by charge‐transfer antennae presents remarkable one‐ and two‐photon photophysical properties in water and an excellent brightness suitable for bio‐imaging applications.